Simulation and prediction of wetland vegetation type based on CA-Markov model - D.J. Guan; S.J. Qu; S.S. Yang; Y.X. Zeng (International Association of Lowland Technology, 2018)
The construction of The Three Gorges Reservoir has changed wetland vegetation type and reconstituted Hydro-fluctuation belt pattern. In this paper, we use the improved method to extract the Hydro-fluctuation belt with clear boundary and four types of wetland land use types, and analyze the dynamic changes of wetland land use types through the area change and structural change. The CA-Markov model is used to simulate the distribution map of the wetland utilization type in the next 20 years. The results show that the vegetation coverage stability of the fluctuate belt has improved; the activity of each type is reduced and the stability is enhanced; the transfer of the terrestrial plants is affected by the bare soil, and the water body has a great influence on the centroid transfer of the hygrophyte; it can be seen from the prediction of the distribution pattern of the future Hydro-fluctuation belt that the stability of the Hydrofluctuation belt will gradually decrease if the environment of the Hydro-fluctuation belt is not protected by human intervention.